1995
DOI: 10.1002/app.1995.070581218
|View full text |Cite
|
Sign up to set email alerts
|

High‐pressure viscosity and density of polyethylene solutions in n‐pentane

Abstract: SYNOPSISViscosity and density of homogeneous one-phase solutions (1 wt %) of polyethylenes with narrow molecular weight distributions ( M , = 2150, 15,520, 108,000, and 420,000) in npentane were determined at 398,413, and 428 K over a pressure range from 20 to 60 MPa. Measurements were done with a special falling cylinder type viscometer that permits simultaneous determination of viscosity, density, and phase state of the solutions. It is shown that the viscosities of these solutions can be correlated with den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 28 publications
6
28
0
Order By: Relevance
“…It is observed that flow activation energies show a small increase with increasing pressure which has also been observed by others [54,55] showing that at higher pressure the viscosity becomes more temperature dependent for this system. …”
Section: Viscosity Of Pe + N-pentane Solutionssupporting
confidence: 62%
See 4 more Smart Citations
“…It is observed that flow activation energies show a small increase with increasing pressure which has also been observed by others [54,55] showing that at higher pressure the viscosity becomes more temperature dependent for this system. …”
Section: Viscosity Of Pe + N-pentane Solutionssupporting
confidence: 62%
“…The activation volumes increase with temperature but observed to decrease with pressure. Activation volumes are higher when compared with values reported for 1 wt % solutions of different molecular weight PE samples in n-pentane [54] that are shown in Table 5.10., which may be due to the higher concentration of the polymer. Ln(viscosity), mPa.s…”
Section: Ln(viscosity Mpasmentioning
confidence: 50%
See 3 more Smart Citations